Sistem Penilaian Kinerja Karyawan Dengan Metode 360 Degree Feedback (Studi Kasus PT Syahid Husada Dewata) - Sjamdra, Ramadhany Krismaliq; Putra, I Gusti Ngurah Alit Widana; Lusiani, Titik (Jurnal Sistem Informasi Universitas Dinamika, 2021)
PT Syahid Husada Dewata is a company engaged in the marketing and maintenance of laboratory equipment located in Bali. If employees whose performance falls below the performance standard, it can hamper transactions. Currently assessment uses Essay method, carried out by one assessor, performance appraisal if done with one perspective can lead to subjectiveity. Current assessment are still in descriptive making it difficult to rank the employees. The solution implemented to overcome these problems is to create an Employee Performance Appraisal System with the 360 Degree Feedback. The application of the 360 Degree Feedback Method used to increase the point of view of appraisal. In order to make it easier rank employees, it’s necessary to convert a descriptive assessment into a scale. Graphic Rating Scale method is used so that the final results of the assessment can be immediately determined for the best ranking of employees. The results obtained from this study are in the form of a performance appraisal system that can be used to take assessments from parties around the assessed employee. The resulting performance appraisal report can be directly used to rank employees. The resulting system also meets the testing phase and meets the design needs of users.